Pendampingan Persiapan Akreditasi POS PAUD RESTU BUNDADesa Durensewu Kecamatan Pandaan Kabupaten Pasuruan - Anifah, Siti (Humanist Journal, 2022)
Accreditation is an assessment process from the government to determine the quality and quality of an institution based on criteria set by the government. More and more people are aware of the importance of education, it turns out to be one of the factors in the development of PAUD institutions in Indonesia, but there are still some PAUD institutions that have not carried out the accreditation process because the issue of accreditation is a scary moment so that institutions experience many obstacles in the process of preparing for accreditation, both principals, teachers. , administration staff. This mentoring activity aims to provide an understanding to institutions of the importance of an accreditation and provide direction in accordance with accreditation assessment standards and by using workshop methods, lectures, questions and answers and the practice of making accreditation documents and uploading documents in the SISPENA application. This activity was carried out on Saturday-Sunday, 18-19 July 2022 at the Restu Bunda PAUD Post Institute, Durensewu Village, Pandaan District, Pasuruan Regency. With this training, teachers can better understand and understand what they will prepare during the accreditation process